Discriminative detection of low‐abundance point mutations using a PCR/ligase detection reaction/capillary gel electrophoresis method and fluorescence dual‐channel monitoring. Issue 8 (25th March 2014) - Hamada, Mariko; Shimase, Koji; Tsukagoshi, Kazuhiko; Hashimoto, Masahiko
<x xml:space="preserve">Abstract</x> We applied a facile LIF dual‐channel monitoring system recently developed and reported by our group to the polymerase chain reaction/ligase detection reaction/CGE method for detecting low‐abundance point mutations present in a wild‐type sequence‐dominated population. Mutation discrimination limits and signaling fidelity of the analytical system were evaluated using three mutant variations in codon 12 of the K‐ras oncogene that have high diagnostic value for colorectal cancer. We demonstrated the high sensitivity of the present method by detecting rare mutations present among an excess of wild‐type alleles (one mutation among ∼100 normal sequences). This method also simultaneously interrogated the allelic compositions of the test samples with high specificity through spectral discrimination of the dye‐tagged ligase detection reaction products using the dual‐channel monitoring system.